Responsibilities of Medical Practice through Digital Health Platforms - Nanda, Wella Mareta; Prilian Cahyani, S.H., S.AP., M.H; Mohamed Ali El Fetouhi Abarran (Yuridika, 2024)
Medical practice through digital health platforms is one of the innovations in the health sector that changes the practice of medicine in a modern direction with technological intermediaries. Digital health platforms accommodate doctors in providing medical services to patients virtually. Certain parties may experience the disadvantages of using technology as a result of limitations that surround medical practice through digital health platforms. The laws have not yet provided specific arrangements related to the medical practice through digital health platforms. This research aims to provide legal certainty by identifying and analyzing the limits of liability of the parties involved in medical practices through digital health platforms. This legal research uses a statutory approach and conceptual approach. The results showed that the imposition of liability for losses suffered by a particular party is based on the element of error inherent in the party that caused the loss. Platform operators are responsible for the leakage of a patient's personal data and medical records. Doctors are responsible for misdiagnosis and prescribing of drugs after the patient provides correct health information. The courier delivery is responsible for ensuring the medicine reaches the patient from the pharmacy according to the prescription given by the doctor. The electronic payment company must solve the transfer of funds problem and the insurances responsible for taking care on insurances needs if the patient connects the treatment with their insurance.